Application of Ileobladder for Clinical Kidney Transplantation: Two Case Reports. (July 2018) - Haberal, Mehmet; Kirnap, Mahir; Akdur, Aydincan; Ayvazoglu Soy, Ebru H.; Yildirim, Sedat; Moray, Gokhan; Kayhan, Zeynep; Torgay, Adnan
Abstract : Introduction: Renal transplantation (RT) is the best treatment option in patients with end-stage renal failure (ESRF). Despite all advances, small, poor compliant or unstable bladders are one of the major problems that we face in RT. Structural urologic abnormalities resulting in dysfunctional lower urinary tract leading to ESRF may constitute 15% patients in the adult population and up to 20-30% in the pediatric population. Although many studies have been performed since more than a century, no distinct method has been developed. This clinical study aims to provide urinary storage, protect the upper urinary tract and preserve renal function, provide continence, resistance to infection and offer a convenient method of voluntary and complete emptying Materials and Methods: We first applied the experimental ileobladder technique to pigs and rats to combat low bladder volume problem one year ago. When this technique proved to be successful in the laboratory environment, we applied this technique to 2 patients with bladder volume problems and ESRF. One patient was 3 years old and had a bladder capacity <2 mL. The other was 4 years old and had a bladder capacity <10 mL Ileobladder technique was performed on the patients with a lower midline incision. RT was performed in the first patient 28 days and in the second patient 44 days after the ileobladder procedure Results: Approximately 15 cm of the ileum segment was prepared for ileobladder 20 cm after terminal ileum, preserving the mesentery. An abdominal lower midline incision was made, exposing the bladder that was transversally opened approximately 2-3 cm. The ileal loop was then anastomosed to the bladder. Two weeks later, living donor RT (from the mother in one patient, and the father in the other) was performed on both patients using standard technique. Since the early postoperative period, creatinine levels have reached normal levels in both patients. On the 15th postoperative day, urine probes were removed. Now, 2 months since surgery, the general condition is good in both patients and no complications were found. Conclusions: The technique of ileobladder was performed successfully for patients with very small bladders. It is our plan to continue this technique to overcome small bladder and neurogenic bladder problems.